ANALYSIS OF THE INFLUENCE OF EMPLOYEE PERFORMANCE IN THE ELELIM REGIONAL COORDINATOR IN SUPPORTING PIONEERING AIR TRANSPORT SUBSIDY SERVICES - Genos Imanuel Bless; Ferdinandus Christian; Rina Astini (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Pioneer Air Transportation is a mode of air transportation that provides air transportation services, and is a form of government intervention by providing subsidies due to an imbalance between demand and supply. This research aims to find out whether work facilities and communication influence employee performance with work motivation as an intervening variable at the Regional Coordinator of Perintis Elelim Airport. The research was conducted on 80 people using saturated sampling techniques. The data collection technique used is primary data in the form of a questionnaire and secondary data obtained through documentation studies. The data analysis technique uses quantitative data processed with the Smart PLS version 3 program, namely validity and reliability testing, hypothesis testing and sobel testing. The results obtained in this study show 1) there is a significant influence between work facilities on performance, 2) there is a significant influence between communication variables on performance, 3) there is a significant influence between work motivation variables on performance, 4) there is a significant influence between work facilities variables on work motivation, 5) there is a significant influence between communication variables on work motivation, 6) work motivation variables can influence work facility variables on performance, 7) work motivation variables can influence communication variables on performance.